Jean-Léo: Le Baron Brisse, un Gastronome du Second Empire - Davidson, Alan E (Petits Propos Culinaires, 2024)
Jean-Léo: Le Baron Brisse, un Gastronome du Second Empire: Brussels, Le Grenier du Collectionneur (Avenue du Polo 88A, 1150 Bruxelles), 1992: 92 pp, numerous b/w illustrations, bibliography, full index, large format paperback, 940 Belgian francs (just over £15.00).